Free Nucleic Acids in the ChAdOx1 nCov-19-S Adenovirus Vector Vaccine Contribute to an Anti-platelet Factor 4 Antibody Response - Siegerist, Florian; Reder, Alexander; Palankar, Raghavendra; Wesche, Jan; Müller, Luisa; Michalik, Stephan; Brandt, Jens van den; Hoppen, Jens; Schönborn, Linda; Thiele, Thomas; Völker, Uwe; Endlich, Nicole; Greinacher, Andreas (Thrombosis and Haemostasis, 2025)
Vaccination against SARS-CoV-2 was instrumental in controlling the COVID-19 pandemic. Rare cases of vaccine-induced immune thrombocytopenia and thrombosis (VITT) emerged following vaccination with the adenovirus vector-based vaccines ChAdOx1 nCov-19-S and Ad26.COV2.S. VITT is mediated by high-titer IgG anti-platelet factor 4 (PF4) antibodies that activate platelets, leading to thrombosis and thrombocytopenia. Similar antibodies have been detected following natural adenovirus infections, suggesting a common immunological trigger. This indicates that a constituent of adenovirus is relevant. Adenovirus is a DNA virus. Virion-unbound viral DNA is present in natural adenovirus infections.To identify whether free virion-unbound DNA is present in ChAdOx1-nCoV19 vaccine and whether adenoviral DNA enhances the immune response to PF4 in mice.We assessed ChAdOx1 nCov-19-S for virion-unbound DNA and differentiated free human and free adenovirus DNA by sequencing. We immunized mice with ChAdOx1 nCov-19-S and its fractions, in which we removed proteins by proteinase K and/or DNA by DENERASE.Using ultracentrifugation and proteinase K digestion, we isolated and characterized free nucleic acids, confirming the presence of both adenoviral and host cell-derived DNA in ChAdOx1 nCov-19-S. Mice immunized with PF4 in combination with ChAdOx1 nCov-19-S or its virion-free supernatant—but not with PF4 alone—developed a strong anti-PF4 IgG response, an effect completely abolished by nuclease (DENARASE) treatment.Virion-unbound DNA in ChAdOx1 nCov-19-S contributes to anti-PF4 antibody formation. This highlights the potential of reducing virion-unbound DNA in vaccine formulations to mitigate unintended immune responses to PF4.
Keywords: VITT; COVID-19; vaccine; platelet factor 4; DNA; adverse reactions; platelets